(untitled) (Research, Society and Development, 2023)
The perianal region in canines is composed of specific cellular and glandular groups that can give rise to different types of neoplasms. One of the main malignant tumors in this site is anal sac adenocarcinoma, which affects the apocrine glands of the anal sac in older dogs. The diagnosis of this neoplasm is made through a combination of clinical, cytological, and/or histological information. Treatment involves tumor excision combined with chemotherapy or radiotherapy, and the prognosis is guarded. This report aims to describe the surgical case of a 9-year-old neutered male West Terrier canine that presented with an enlargement in the right perianal region due to anal sac adenocarcinoma, which was treated with surgical excision.